The Historical Boom of Stylistics and its Imprint in Costa Rica - Villalobos, Carlos Manuel (Journal of Philology and Linguistics of the University of Costa Rica, 2020)
This paper studies the historical impact of stylistics and its effects in Costa Rica. It is based on a publication made by Manuel Picado in 1975 where he summarizes the postulates of stylistics according to Amado Alonso. This methodology of analysis of verbal expression emerged in the early twentieth century as part of structural linguistics, but its main applications were in the field of literary studies. Through the style, manifested in the form, the creative spirit is accessed, either to value a specific author or to characterize a cultural group. The paper studies its passage through the idealist schools of Germany and Spain and the boom it had in Latin America. In the last part, is analyzed the mark that it left in Costa Rican literary studies: from the study of style in the framework of the literary prescriptive to the first stylistic glimpses with Roberto Brenes Mesén and Arturo Agüero Chaves. In this context, the work of Abelardo Bonilla of 1967 stands out. He tried to explain, with literary examples, the style of the Costa Rican spirit.